Light-induced solubility modulation of polyfluorene to enhance the performance of OLEDs - Schelkle, Korwin; Bender, Markus; Jeltsch, Krischan; Buckup, Tiago; Müllen, Klaus; Hamburger, Manuel; Bunz, Uwe H. F. (Angewandte Chemie. International edition, 2015)
Liquid-phase processing is a key prerequisite for the cost-efficient fabrication of organic electronic devices. We report an approach for light-induced modulation of the solubility of π-conjugated polymers (polyfluorene) with side chains functionalized with hydroxycinnamic acid. Irradiation with light cleaves the solubilizing side chains and renders the thin films of the polyfluorene insoluble. In a proof of concept device, polyfluorenes were applied as emissive layers in OLEDs. Photoirradiation of the emission layer leads to an increase in OLED performance combined with a modulation of the solubility of the thin film. These results offer the possibility for further development in terms of manipulating the solubility and emissive parameters of an important class of functional materials.